Transforming PT Pertamina with Cybersecurity, File Security, and Essential Items - Rama Azhari; Agita Nisa Salsabila (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2023)
Considering the threat posed by cyberattacks, terrorist acts, and security breaches, it is imperative to implement an effective security policy to safeguard important items. Cybersecurity is yet another important topic covered in this study. PT Pertamina is a company that relies heavily on computer networks and information technology. Cyberattack defense and computer system security are critical components of PT Pertamina's operating performance. Consequently, to stop cyberattacks, data theft, and the leakage of private information, an efficient cyber security plan must be put into place. This paper also focuses on file security. Financial data, customer information, and contract agreements are just a few of the crucial items that PT Pertamina maintains and keeps track of. It is essential to protect these files to stop illegal access, data theft, and other threats to the business's operations. This essay will examine many tactics and approaches that PT Pertamina might use to implement file security, cyber security, and vital objects. It is hoped that this paper will act as a guide for PT Pertamina and other similar businesses in safeguarding their valuable assets against security-related internal and external threats.